How Do We Perceive a Humorous Manager? Manager Humor, Impression Management, and Employee Willingness to Work With the Manager - Brender-Ilan, Yael; Reizer, Abira (Frontiers in Psychology, 2021)
Humor is a form of communication that is intended to be entertaining and produce positive affective and cognitive responses from receivers. Nonetheless, humor in the workplace is a complicated matter. It has been recognized as a valuable tool for managers because it can activate various favorable outcomes and alter employees' perception of the manager's warmth and competence (impression management), but not always to the benefit of the manager. In our studies, the use of humor showed changed attitudes toward a manager’s warmth and competence, and eventually influenced the employee’s behavioral intentions. In Study 1, we tested the use of managerial humor in two emails. The humorous manager was perceived as warm, but not competent. Impression management mediated the employee's willingness to work with the manager. In Study 2, we tested the use of managerial humor with one introductory email. In this study, we also monitored the gender of both the manager and the employee. Once again, the humorous manager was perceived as warm and humor mediated employees' behavioral intentions. As for competence, gender moderated the results, such that male employees perceived humorous female managers as more competent, while female employees perceived humorous male managers as less competent. Practical implications are presented.